2020
DOI: 10.1111/cen.14276
|View full text |Cite
|
Sign up to set email alerts
|

Low serum 25‐hydroxyvitamin D (25[OH]D) levels in patients hospitalized with COVID‐19 are associated with greater disease severity

Abstract: Summary Objectives Vitamin D deficiency (VDD) has been proposed to play a role in Coronavirus Disease 2019 (COVID‐19) pathophysiology. We aim to evaluate our implementation of a local protocol for treatment of VDD among patients hospitalized for COVID‐19; to assess the prevalence of VDD among COVID‐19 inpatients, and examine potential associations with disease severity and fatality. Design and Participants We conducted a retrospective interim audit of a loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
161
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 10 publications
21
161
5
3
Order By: Relevance
“…Nevertheless, neither mortality nor duration of hospitalization was associated with the vitamin D status [25]. Likewise, other small series reported a higher prevalence of 25OH-vitamin D deficiency in the patients with a worse outcome [26] or in those requiring ICU admission [27] In conclusion, our results do not support the hypothesis of a specific role of the vitamin D deficiency in the risk of COVID-19 infection. In fact, no differences were found between the 25OH-vitamin D levels of the patients affected by COVID-19 related pneumonia and those of other patients hospitalized because of other acute illnesses.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, neither mortality nor duration of hospitalization was associated with the vitamin D status [25]. Likewise, other small series reported a higher prevalence of 25OH-vitamin D deficiency in the patients with a worse outcome [26] or in those requiring ICU admission [27] In conclusion, our results do not support the hypothesis of a specific role of the vitamin D deficiency in the risk of COVID-19 infection. In fact, no differences were found between the 25OH-vitamin D levels of the patients affected by COVID-19 related pneumonia and those of other patients hospitalized because of other acute illnesses.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been suggested that supplementation of vitamin D at an oral dose of 200,000 to 300,000 international units (IU) and other micronutrients for a week can strengthen the immune system against COVID-19 [ 96 , 97 ]. An observational study also demonstrated an inverse relationship between the critical outcome of COVID-19 and serum levels of 25 hydroxyvitamin D (25(OH)D) [ 98 ]. However, in contrast, a study from the UK reported no statistical relationship between serum 25(OH) D level and COVID-19 [ 99 ].…”
Section: Vitamins and Immune Systemmentioning
confidence: 99%
“…Patients with severe ARDS [10,11] or requiring ICU [12] are frequently severely vitamin D deficient [13]. In addition, low serum 25-hydroxyvitamin D (25[OH]D) levels in patients hospitalized with COVID-19 are associated with greater disease severity [14]. Vitamin D treatment has been found to decrease other viral respiratory infections, especially in persons with vitamin D deficiency [15].…”
Section: Discussionmentioning
confidence: 99%